PENGELOLAAN KELAS UNTUK MENGATASI KONSENTRASI BELAJAR AGAMA ISLAM PERSPEKTIF WILLIAM GLASSER - Ramadani, Muhammad Fikri; Cindy Faradillah, Riska Aulia; Syafi'i, Imam (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2025)
Classroom management is a crucial aspect in ensuring the effectiveness of learning, especially in the context of Islamic Religious Education (PAI) which often faces the challenge of low student learning concentration. This article aims to examine the management of Choice Theory-based classrooms developed by William Glasser as a strategy to increase students' learning concentration in PAI lessons. The research method used is a literature study by analyzing secondary sources such as books, journals, and other academic documents. The results of the study show that classroom management according to Choice Theory emphasizes the fulfillment of five basic needs of students: survival, love and belonging, power, freedom, and fun. Fulfilling these needs creates a learning environment that is conducive, motivating, and fosters students' self-awareness. In addition, the WDEP (Want, Doing, Evaluation, Planning) approach in Choice Theory plays an important role in helping students develop self-awareness and responsibility for their learning process. By integrating these principles in classroom management, PAI teachers can transform into adaptive and empathetic facilitators in managing the diversity of character and needs of students.